The manly art : bare-knuckle prize fighting in America - Gorn, Elliott J., 1951- (Cornell University Press, 2010)
"Elliott J. Gorn's The Manly Art tells the story of boxing's origins and the sport's place in American culture. When first published in 1986, the book helped shape the ways historians write about American sport and culture, expanding scholarly boundaries by exploring masculinity as an historical subject and by suggesting that social categories like gender, class, and ethnicity can be understood only in relation to each other. This updated edition of Gorn's highly influential history of the early prize rings features a new afterword, the author's meditation on the ways in which studies of sport, gender, and popular culture have changed in the quarter century since the book was first published."--Publisher's Web site.